THE CONCEPT OF AGGRESSION IN THE ENGLISH DISCOURSE OF WAR: A COGNITIVE-SEMANTIC DIMENSION - Shevchenko, Vadym (Philological Treatises, 2024)
This article focuses on the construction of the meanings of AGGRESSION that are profiled in different domains of the world construal. The purpose of this article is to identify the semantic features of nominations of AGGRESSION in English and to model the concept of AGGRESSION in the English-language discourse of war, in particular, russia's full-scale military aggression against Ukraine. The relevance of the object of study is determined by the importance of the russia-Ukraine war as today’s global threat and is reinforced by the use of a cognitive-semantic and conceptual approaches to its study. The article proposes and proves a hypothesis about the attributive nature of the concept of AGGRESSION, which in the world construal is profiled in the segments of WAR and PEACE and has semantic qualities and conceptual features specific to each of them. The study was conducted in three stages according to the degree of generalization and abstraction of the data. At the first stage, the lexical set of concept nominations was systematized, and the semantic space of AGGRESSION was outlined. At the second stage, the semantic network of concept names profiled in the WAR segment of the world construal was modeled. The most typical ways of schematic generalization of meanings prove to be the object frame and identification frame, while the action frame is limited to the contact action scheme. At the third stage, AGGRESSION was modeled on the basis of the cognitive operation of highlighting / prominence of meanings. The study concludes that in the English-language discourse of war, AGGRESSION is an attributive poly-appealed concept that is profiled in the WAR segment of the world construal and is defined as a contact offensive action initiated by the aggressor, violent, unreasonable and unprovoked, threatening to foreign territory and civilians; it is distinguished by cruelty and bloodshed, it is of terrorist and genocidal nature.